2020
DOI: 10.1097/psy.0000000000000900
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mindfulness and Meditation on Vagally Mediated Heart Rate Variability: A Meta-Analysis

Abstract: Objective: Heart rate variability (HRV) is a marker of autonomic nervous system function associated with both physical and mental health. Many studies have suggested that mindfulness and meditation-based interventions (MBIs) are associated with improvements in HRV, but findings are mixed, and to date, no comprehensive meta-analysis has synthesized results. Methods: Systematic literature searches were conducted using PsycINFO, Embase, Medline, CINAHL, ERIC, and Scopus to identify randomized controlled trials (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 71 publications
2
16
0
3
Order By: Relevance
“…Our results are consistent with previous research showing that brief mindfulness interventions can enhance HRV [ 32 , 33 ]. The overall effects of the MBI on HRV measures were small, in line with other studies; for a review, see Rådmark et al [ 34 ], although the results in this area are mixed [ 35 ]. Even though the effect size was small, these results are particularly important.…”
Section: Discussionsupporting
confidence: 82%
“…Our results are consistent with previous research showing that brief mindfulness interventions can enhance HRV [ 32 , 33 ]. The overall effects of the MBI on HRV measures were small, in line with other studies; for a review, see Rådmark et al [ 34 ], although the results in this area are mixed [ 35 ]. Even though the effect size was small, these results are particularly important.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, it has been shown that HRV can be modulated during the practice of meditation 106 . However, a recent meta-analysis on this exact matter found insufficient evidence suggesting mindfulness/meditation led to improvements in vagally mediated HRV, and more well-designed RCTs without high risk of bias are needed to clarify any such contemplative practices’ impact on this physiological metric 107 , along with potential mechanisms related to cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the last decade, the field of studies examining the effects of various mind-body-interventions (MBI) on HRV has grown. These involved studies on yoga ( 1 – 3 ) as well as mindfulness and other meditative interventions ( 4 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the influence of yoga on HRV, some positive effects were found in systematic reviews and meta-analyses, but with the limitation of an overall insufficient study quality and partly contradictory results ( 1 , 3 ). A recent meta-analysis on mindfulness and meditation concluded that there is currently insufficient evidence to indicate that MBIs lead to improvements in HRV over control conditions ( 8 ). Still, MBIs are increasingly used in the treatment of depression and HRV has been suggested as an indicator of success ( 27 ) or predictor of the outcome in depression treatment ( 28 ).…”
Section: Introductionmentioning
confidence: 99%